Jute Fibers Synergy with Nzvi/Go: Superficial Properties Enhancement for Arsenic Removal in Water with Possible Application in Dynamic Flow Filtration Systems - Sepúlveda-Ortiz, P; Sepúlveda-Ortiz, P (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Groundwater is one of the primary sources of water for both drinking and industrial use in northeastern Mexican territory, around 46% of the total, due to the lack of precipitation during the year and solar radiation index. The presence of arsenic in brackish soil and groundwater is a severe health issue, specifically in semi-arid and arid regions in the north of Mexico. Additionally, it represents the only source of drinking water in communities far from big cities, mainly due to the absence of hydric infrastructure. This work presents a new approach to treating polluted water with arsenic. The system based on activating jute fiber with nanoparticles of zero-valent iron immobilized over graphene oxide will allow nZVI particles to preserve their unique qualities for water sanitization. A dynamic flow test was designed to determine the effectivity of activated jute fibers as a water sanitation system. The results showed a reduction in the total arsenic content from 350 ppb to 34 ppb with a filtrate flow of 20 mL/min. The above represents 90% adsorption by the activated fiber. The analyzed sample corresponds to contaminated groundwater taken from Coahuila, Mexico. This sanitation system could be applied to low-income populations lacking robust infrastructure, such arsenic treatment plants. © 2022 by the authors.